2014
DOI: 10.4137/cmc.s17067
|View full text |Cite
|
Sign up to set email alerts
|

Fatty Acid-Binding Protein 4 (FABP4): Pathophysiological Insights and Potent Clinical Biomarker of Metabolic and Cardiovascular Diseases

Abstract: Over the past decade, evidences of an integration of metabolic and inflammatory pathways, referred to as metaflammation in several aspects of metabolic syndrome, have been accumulating. Fatty acid-binding protein 4 (FABP4), also known as adipocyte FABP (A-FABP) or aP2, is mainly expressed in adipocytes and macrophages and plays an important role in the development of insulin resistance and atherosclerosis in relation to metaflammation. Despite lack of a typical secretory signal peptide, FABP4 has been shown to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
331
0
8

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 306 publications
(351 citation statements)
references
References 160 publications
(245 reference statements)
12
331
0
8
Order By: Relevance
“…The long-chain monosaturated FFA oleate has been shown to be able to stimulate the proliferation of human breast cancer cells, with PI3K having a role in this process (Hsu et al, 2007;Hardy et al, 2005). Of note, FABP4 is an adipose tissue-secreted adipokine involved in the regulation of energy metabolism (Furuhashi et al, 2014), and plays an important role in FA uptake by cells (Wu et al, 2014). A recent study demonstrated that exogenous FABP4 can positively regulate cancer cell proliferation through the activation of PI3K-AKT and MAPK-ERK pathways in breast cancer cells (Guaita-Esteruelas et al, 2016).…”
Section: Circulating Free Fatty Acidsmentioning
confidence: 99%
“…The long-chain monosaturated FFA oleate has been shown to be able to stimulate the proliferation of human breast cancer cells, with PI3K having a role in this process (Hsu et al, 2007;Hardy et al, 2005). Of note, FABP4 is an adipose tissue-secreted adipokine involved in the regulation of energy metabolism (Furuhashi et al, 2014), and plays an important role in FA uptake by cells (Wu et al, 2014). A recent study demonstrated that exogenous FABP4 can positively regulate cancer cell proliferation through the activation of PI3K-AKT and MAPK-ERK pathways in breast cancer cells (Guaita-Esteruelas et al, 2016).…”
Section: Circulating Free Fatty Acidsmentioning
confidence: 99%
“…Possible mechanisms of reduced FABP4 concentration caused by sitagliptin. FABP4 is secreted from adipocytes in association with lipolysis and may act as an adipokine for the development of insulin resistance and atherosclerosis, leading to cardiovascular events ( 3,9 ). Sitagliptin, a DPP-4 inhibitor, slows GLP-1 degradation, thereby increasing endogenous GLP-1 concentration.…”
Section: Studymentioning
confidence: 99%
“…Finally, we cannot exclude the possibility that the effect of sitagliptin on serum FABP4 level was partly mediated by changes in expression and secretion of FABP4 in cells other than adipocytes. There has been accumulating evidence indicating FABP4 is expressed in several types of cells, in addition to adipocytes and macrophages, under both physiological and pathological conditions ( 3,(51)(52)(53)(54)(55), though the predominant contributors of circulating FABP4 level are adipocytes rather than macrophages or other types of cells ( 3,9 ).…”
Section: Studymentioning
confidence: 99%
“…Despite being intracellular proteins, FABP are released into the circulation and its increased plasma levels had found in several clinical conditions and proposed as markers of tissue injury (6) . Plasma AFABP levels are increased in metabolic disorders as obesity, type-2 diabetes mellitus (9) and cardiovascular conditions (10) , and in critically-ill patients and correlate with poor prognosis (11) .…”
mentioning
confidence: 99%